2020
DOI: 10.1177/1073191120952885
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Effect of Varying the Number of Response Alternatives in Clinical Assessment: Evidence From Measuring ADHD Symptoms

Abstract: This study illustrated the effect of varying the number of response alternatives in clinical assessment using a within-participant, repeated-measures approach. Participants reported the presence of current attention-deficit/hyperactivity disorder symptoms using both a binary and a polytomous (4-point) rating scale across two counterbalanced administrations of the Current Symptoms Scale (CSS). Psychometric properties of the CSS were examined using (a) self-reported binary, (b) self-reported 4-point ratings obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Methodologically, the performance behavior of different Likert scale lengths can be studied using two approaches either through experimentation (Donnellan and Rakhshani, 2020;Kutscher and Eid, 2020;Shi et al, 2021) or using computer simulation (Goggin and Stoker, 2014;Sangthong, 2020). Experimental study has several advantages that empirically consider the psychological aspects of respondents that were unable to be explained by the simulation study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodologically, the performance behavior of different Likert scale lengths can be studied using two approaches either through experimentation (Donnellan and Rakhshani, 2020;Kutscher and Eid, 2020;Shi et al, 2021) or using computer simulation (Goggin and Stoker, 2014;Sangthong, 2020). Experimental study has several advantages that empirically consider the psychological aspects of respondents that were unable to be explained by the simulation study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works reported that there were several statistical measures that have been examined to evaluate the experimental setting of different Likert scale lengths. They were reliability (Donnellan and Rakhshani, 2020), discrimination index (Alan and Kabasakal, 2020;Daher et al, 2015;Goggin and Stoker, 2014;Freihat, 2019;Garner, 1960;Weng, 2004), criterion validity (Simms et al, 2019), factor analysis (Shi et al, 2021), inferential statistics (Sangthong, 2020), polytomous item response theory (Kutscher and Eid, 2020), Rasch model (Daher et al, 2015;Ilhan and Guler, 2017), structural equation modeling (Maydeu-Olivares et al, 2009), and information theory (Green and Rao, 1970;Miller, 1956;Parducci and Wedell, 1986) (Hambleton et al, 1991;Harwell and Gatti, 2001;Lee and Paek, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Such response levels are regarded as ordinal steps along a presumed continuous dimension and the Likert format is generally preferred over a simpler yes–no format that forces respondents to express only all–or–none positions. Thus, switching from just two (i.e., yes–no) to more response alternatives per item is regarded as allowing for finer granularity that, in turn, might result in more precise measures or more ability to discriminate respondents from one another (see, for example, Alan & Kabasakal, 2020 ; Donnellan & Rakhshani, 2023 ; Maydeu-Olivares et al, 2009 ; Müssig et al, 2022 ; Shi et al, 2021 ). In the limit, a continuous response format can be implemented via a visual analog scale (VAS) on which respondents mark any position along a continuous line, limited only by the resolution with which the mark can be made and subsequently read off.…”
mentioning
confidence: 99%